1984
DOI: 10.1099/00221287-130-12-3295
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Wall Glucans from Yeast, Hyphal and Germ-tube Forming Cells of Candida albicans

Abstract: Acid-soluble and alkali-insoluble glucan fractions were prepared from yeast, hyphal and germtube forming cells of Candida albicans. Alkali-insoluble glucan was also extracted from purified yeast cell walls. Paper chromatography of partial acid hydrolysates confirmed that the glucan preparations contained fl( 1+3)-and p( 1+6)-chains but no mixed intra-chain p( 1+3)/( 1+6) linkages. Methylation and 3C-NMR analyses showed that the acid-soluble glucan consisted of a highly branched polymer composed mainly (674% to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 21 publications
2
34
0
Order By: Relevance
“…Presumably, Quantazyme had difficulty in passing ␤-1,6 branch points in the ␤-1,3-glucan polymers present in the cell wall, thereby leaving some undigested ␤-1,3-glucan attached to the ␤-1,6-glucosylated mannoproteins. It is tempting to speculate that the protein-bound ␤-1,6-glucan-␤-1,3-glucan demonstrated here is related to the ␤-1,6-glucan-␤-1,3-glucan heteropolymer isolated from the alkali-soluble wall fraction of C. albicans (1,11,25). Montijn et al (19) have shown that the ␤-1,6-glucose-containing side chains of glucanase-extracted cell wall proteins of S. cerevisiae are not modified or extended N chains and are also not O linked.…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, Quantazyme had difficulty in passing ␤-1,6 branch points in the ␤-1,3-glucan polymers present in the cell wall, thereby leaving some undigested ␤-1,3-glucan attached to the ␤-1,6-glucosylated mannoproteins. It is tempting to speculate that the protein-bound ␤-1,6-glucan-␤-1,3-glucan demonstrated here is related to the ␤-1,6-glucan-␤-1,3-glucan heteropolymer isolated from the alkali-soluble wall fraction of C. albicans (1,11,25). Montijn et al (19) have shown that the ␤-1,6-glucose-containing side chains of glucanase-extracted cell wall proteins of S. cerevisiae are not modified or extended N chains and are also not O linked.…”
Section: Discussionmentioning
confidence: 99%
“…Since only linear polymers of 8-1,3 glucan and chitin are synthesized in vitro [I, 21, while branched glucans [19] and linkages to chitin [20-221 are found in vivo, some form of assembly reactions most likely occur post synthetically for the major structural polymers of fungal cell walls. The most likely candidate enzyme activity would be glycosyltransferases capable of assembling nascent glucan and chitin into the final wall structure.…”
Section: Discussionmentioning
confidence: 99%
“…It is also of interest that second site suppressors containing no (1-*6)-P-D-glucan can at least partially bypass the KRES defect, although in all cases examined, these suppressors grew considerably more slowly than did wild-type cells. The demonstration here that (1-*6)- (14), and as (1--6)-P-D-glucans are apparently absent from mammalian cells, the KRE5 gene product is a new target for antifungals that should show specificity of action.…”
Section: S V N N T a L E S V C S E R I G Y Y T K N E E Y N L L H T I mentioning
confidence: 99%